Peningkatan Hasil Belajar PPKn melalui Penerapan Model Pembelajaran Kooperatif Tipe STAD pada Kelas IX.1 SMPN 1 Keruak - Asri Nurhayani (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2019)
This study aims to determine the increase in PPKN learning outcomes through the application of the STAD type of cooperative learning model for class IX.I students of SMP Negeri 1 Keruak in 2019/2020 Academic Year. This Classroom Action Research is carried out by applying the STAD (Student Teams Achievement Divisions) Cooperative Learning Model in order to improve the quality of the learning process that helps teachers carry out PPKN learning activities taught by means of maximizing the active role of students especially the knowledge they have and how they are applied in daily life -day. This Classroom Action Research (CAR) was conducted in 2 cycles, and the results of the actions that have been carried out are proven to be able to improve student achievement both in terms of completeness of student learning, namely in cycle I by 67%, can be increased to 90% in cycle II or in terms of the average value of the evaluation results in the first cycle of 70.7 to 76.5 in the second cycle, this means there is an increase of 23%. From the results of this classroom action research also showed an increase in the level of student learning activities from 2.83 Active Enough categories in the first cycle to 4.01 Active categories, meaning there was an increase of 1.18.